Pengaruh Entrepreneurship Attitude, Perceived Desirability dan Entrepreneurship Education Terhadap Entrepreneurship Intention pada Siswa Sekolah Menengah Kejuruan - Ninda Firnia Febrinda; Jaka Nugraha (Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to determine the effect of entrepreneurial attitudes, entrepreneurial traits, and entrepreneurship education on entrepreneurial intentions of students majoring in OTKP SMK Ipiems Surabaya. This study uses a quantitative method with a survey approach. This type of research data is primary data derived from direct observation and questionnaire answers. The place for conducting this research is at SMK Ipiems Surabaya. The sampling technique uses saturated samples. Total 56 respondents. Data collection techniques using questionnaires and observations. Data analysis used classical assumption test and multiple linear regression analysis using IBM SPSS application. The results of this study state that there is no influence of entrepreneurship attitude and entrepreneurship education on entrepreneurship intention. The proof is from the results of the T test, where in the SPSS output table it is known that the t value of the entrepreneurship attitude variable is 0.288 <t table 2.019 and the t value of the entrepreneurship education variable is 0.784 <t table 2.019. Meanwhile, perceived desirability has an effect on entrepreneurship intention. The proof is through the results of the T test on the SPSS output table, it is obtained that the t value of the perceived desirability variable is 2.683> t table 2.019.